Avaliação de impacto da gamificação na alfabetização financeira de alunos de escolas públicas - Silva, Rômulo César Reisdorfer da (2024)
The financial literacy of young people in Brazil, and its impact on financial behavior, particularly with regard to indebtedness and the effectiveness of teaching methods in schools, are topics of growing importance. This study integrates two crucial perspectives on the subject: the effect of financial literacy on Generation Z's risk of indebtedness and the effectiveness of using board games as educational tools to teach finance in schools. The first part of the study focuses on the relationship between financial literacy and the risk of debt among Generation Z youth. Using an empirical methodology by means of multiple linear regression, the research collects and analyzes data to assess the level of financial literacy and its dimensions of this age group and how this influences their financial decisions and debt behavior. The central conclusion is that better financial understanding is associated with a significant reduction in the risk of indebtedness, underlining the importance of financial education in shaping healthy financial behavior among young people. The second part of the study explores the use of board games as an innovative methodology for teaching finance in schools. Through a quasi-experiment in which board games with a financial theme were introduced into the classroom, the impact of these games on students' financial literacy was assessed. The results show that board games are an effective tool for teaching financial concepts, contributing to a greater understanding on the part of the students. The importance of effective and innovative educational strategies in promoting financial literacy among young people is evident. The findings indicate that not only is it crucial to integrate financial education into school curricula, but also that innovative methods such as board games can be particularly effective. This work highlights the potential positive impact that such approaches can have on the financial health of young Brazilians, preparing them to make more informed and responsible financial decisions. The research makes a significant contribution to the field of financial education, offering valuable insights for educators, policymakers and financial professionals on how to implement more effective and engaging financial education programs.